Milk somatic cell count and its relationship with feed efficiency, and with GreenFeed-estimated methane emission and energy partitioning variables in Nordic Red cows - Guinguina, Abdulai; Danielsson, Rebecca (Elsevier, 2025)
The objective of this study was to evaluate the relationship of somatic cell count (SCC) with production efficiency, energy partitioning, and methane emission in Nordic Red cows. Data were obtained from 10 previously conducted experiments consisting of 3 milk production trials and 7 GreenFeed (GF) studies, with available information on SCC, body weight (BW), milk production and feed intake. The complete data set consisted of a total of 924 cow/period observations from 265 cows. A subset of 150 cow/period observations from three of the GF studies, with available data on digestibility, and heat production were used for analysing energy partitioning variables. All measurements were made on cows fed diets based on grass silage with a range of protein and energy supplements. Production efficiency and energy partitioning variables were evaluated by mixed-model regression in SAS (SAS Institute Inc., Cary, NC). with the natural logarithm of SCC (lnSCC) treated as a fixed variable. Experiment (Exp), diet(Exp), and period(Exp) were included as random effects, allowing their effects to be excluded from the fixed-effect estimates. Additionally, segmented regression (PROC NLMIXED in SAS) was applied to determine SCC thresholds affecting feed efficiency variables. An increase in lnSCC showed a negative relationship with milk lactose concentration, milk yield, energy corrected milk (ECM), residual ECM, and feed conversion efficiency. Conversely, milk protein concentration increased with rising lnSCC. A trend towards increased BW was noted with rising lnSCC. Methane energy intensity and heat production increased while the efficiency of metabolizable energy (ME) use for lactation (kl) decreased with elevated lnSCC. We identified SCC thresholds of 40 000 cells/mL for heat production (HP) and 74 000 cells/mL for kl, indicating that HP increases at an earlier stage of infection, while a more advanced infection is required to impair energy utilization efficiency. These findings underscore the importance of early SCC management to sustain production, minimize energy losses, and enhance feed efficiency and overall dairy sustainability.
Keywords: feed efficiency; heat production; methane emission; somatic cell count